Influenza transmission indicator – Portuguese experience - Rodrigues, Ana Paula (2018)
Transmission indicator - Weekly Influenza-like illness (ILI) incidence rate (/10^5): National indicator; Availability of denominators (sum of users of each GP that reports ILI cases, even if zero, during the week); Stable surveillance system (since 1989); Timely (paper or web form); A subset of cases is laboratory tested for Influenza.